Historical and social-cultural processes as drivers for genetic structure in Nordic domestic reindeer - Roed, Knut H.; Kvie, Kjersti S.; Bardsen, Bard-J.; Laaksonen, Sauli; Lohi, Hannes; Kumpula, Juoko; Aronsson, Kjell-Å.; Åhman, Birgitta; Vage, Jorn; Holand, Oystein (2021)
We have analyzed DNA microsatellites and the mitochondrial control region in reindeer from 31 different husbandry areas in Norway, Sweden, and Finland in order to better understand the processes that underlie the genetic variability of the Nordic domestic herds. The distinct differentiation found in the nuclear markers but less so in the mitochondrial marker gives evidence of an origin from a common ancestral population which later evolved into the two main gene pools characterizing the nuclear genomes of domestic reindeer in Finland and most of Sweden and Norway. Analyses of temporal trends in effective population size give evidence of a rapid increase in number of reindeer before the population growth associated with the pastoral transition. This implies that the ancestry of contemporary domestic reindeer lay among a rapidly growing wild population possibly located in the boreal areas of eastern Fennoscandia or European Russia. The evolution of reindeer husbandry in Finland, perhaps with input from European Russia, which later spread to northern Norway could explain the shared genomic pattern observed in these areas today. The structured selection of productive female-centered herds may explain the genetic structure in other parts of Norway and in Sweden. The further substructuring of the Swedish/ Norwegian gene pool appears to follow the traditional language borders with the South Sami language dominating the southern and the Central Sami language in the more northern genetic subclusters. This suggests that traditional knowledge, cultural identities, and herd migrations have contributed to shape the genetic structure seen today. Ecological gradients are more pronounced within as compared to between the genetic clusters, giving further evidence that historical and social-cultural processes are important drivers for the genetic differentiations found in domestic reindeer across the Nordic countries.